Collagen properties of Indonesian local sheepskin isolated using acid and enzymatic methods. - Putri, Dita Prameswari Trenggono; Pangestika, Vernanda Widya; Ilyas, Hanifan; Abidin, Mohammad Zainal; Fitriyanto, Nanung Agus; Erwanto, Yuny (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study aimed to investigate the physical properties of Indonesian local sheep skin collagen extracted by acid and enzymatic methods. Materials and Methods: Collagen was isolated from Pure Breed Garut Sheep (Ovis aries sp.) skin, 1.5 years old. The skins were obtained from a local slaughterhouse in Cirebon, Indonesia. The solvents used were CH3COOH and three different enzymes: neutrase, alcalase, and bromelain. Results: The highest yields of extracted collagen were bromelain-soluble collagen (BSC), which reached 37.07%. The range of Ph values for all samples started from 4.01 to 4.76. The viscosity values (cP) of acid-soluble collagen (ASC), neutrase-soluble collagen (NSC), alcalase-soluble collagen (LSC), and BSC were 3.42, 3.90, 3.45, and 3.12, respectively. Regarding SDS-PAGE analyses, Garut sheepskin collagen is categorized as collagen type I, which has a molecular weight of about 140.99 to 148.74 kDa for α1 and around 110 to 111.86 kDa for α2. The results of FTIR and DSC analyses for all samples show the same motif with commercial collagen motifs based on the literature. Conclusion: Garut sheep skin has the potential to be an alternative raw material source for producing collagen. Collagen extracted using a combination of CH3COOH and bromelain enzyme showed the most desirable results in almost every characteristic. J. Adv. Vet. Anim. Res., 11(3): 722–728, September 2024 http://doi.org/10.5455/javar.2024.k823